Financial Flexibility and Corporate Investment: Evidence from a Market-Implied Measure - Ekengren,Anna; Fjellström,Sebastian (2026)
Purpose: The purpose of this study is to examine how the market-implied value of financial flexibility, measured through the VOFF composite of Rapp et al. (2014), relates to firm-level capital investment decisions, and to investigate whether financial flexibility moderates the negative effect of economic policy uncertainty (EPU) on investment. Methodology: The study applies a deductive quantitative research design using panel regressions on U.S.-listed firms. VOFF is constructed following Rapp et al. (2014) as a market-implied measure of the value that shareholders assign to financial flexibility. Theoretical perspectives: The theoretical foundation draws on dynamic capital structure theory, financing-friction models, the precautionary motive for liquidity, and real options theory. Together, these perspectives imply that financial flexibility should be most valuable when external financing is costly and uncertainty raises the value of delaying irreversible investment. Empirical foundation: The final estimation sample consists of 21,001 firm-year observations of U.S.-listed firms on the AMEX, NASDAQ, and NYSE exchanges over the period 2009–2023. Conclusions: The results show that VOFF is positively associated with capital expenditure, while EPU is negatively associated with capital expenditure in specifications where the direct EPU effect can be identified. The positive VOFF × EPU interaction indicates that firms with above-average VOFF experience a smaller investment reduction when policy uncertainty rises. The moderating effect is strongest among smaller firms and low-technology industries.
Keywords: Value of Financial Flexibility; Economic Policy Uncertainty; Capital Investment; Real Options Theory; Investment Sensitivity